2016
DOI: 10.1111/anae.13522
|View full text |Cite
|
Sign up to set email alerts
|

General anaesthesia vs. conscious sedation for transfemoral aortic valve implantation: a single UK centre before-and-after study

Abstract: SummaryReported data suggest that 99% of transfemoral, transcatheter aortic valve implantations in the UK are performed under general anaesthesia. This before-and-after study is the first UK comparison of conscious sedation vs. general anaesthesia for this procedure. Patients who underwent general anaesthesia received tracheal intubation, positive pressure ventilation, radial arterial and central venous access and urinary catheterisation. Anaesthesia was maintained with propofol or sevoflurane. Patients who re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 28 publications
0
35
1
1
Order By: Relevance
“…In terms of catecholamine administration, inotropes are preferable over vasopressors, since poor contractility and left ventricular systolic dysfunction are dominating factors in the genesis of hypotension in TAVI patients. 42 Additionally, Goren et al explained the lower rate of red blood cell transfusions they found in patients who underwent LAS in terms of anaesthesiologists' increased tolerance of low haemoglobin values as long as haemodynamic stability is maintained. 29 According to Palermo et al, increased blood loss in the GA group is considered secondary to the vasodilating effect of halogenic volatile anaesthetics.…”
Section: Length Of Staymentioning
confidence: 99%
“…In terms of catecholamine administration, inotropes are preferable over vasopressors, since poor contractility and left ventricular systolic dysfunction are dominating factors in the genesis of hypotension in TAVI patients. 42 Additionally, Goren et al explained the lower rate of red blood cell transfusions they found in patients who underwent LAS in terms of anaesthesiologists' increased tolerance of low haemoglobin values as long as haemodynamic stability is maintained. 29 According to Palermo et al, increased blood loss in the GA group is considered secondary to the vasodilating effect of halogenic volatile anaesthetics.…”
Section: Length Of Staymentioning
confidence: 99%
“…One of them might be the safe and reliable working conditions for the cardiologist, especially due to the avoidance of sudden, uncontrolled movements of the patient under CS that might endanger the success of the procedure. The frequent concerns expressed about the safety of CS‐concepts for TF‐TAVI, especially in light of acute procedural‐related complications that need immediate modification of the anaesthesia management, have recently been refuted by several investigations, and similarly highlighted by our results . With respect to the necessity to convert from CS to GA, we report on a conversion of 5 times (5.1%).…”
Section: Discussionmentioning
confidence: 51%
“…With the risk of generating further statistically and clinically significant differences between the cohorts (beyond age and history of hypertension), we elected to simplify the match to minimise the risk of a negative impact on the data set. Marshall et al showed that using a linearly-designed cognitive aid improves treatment of anaphylactic reactions during anaesthetic simulations [1], in accordance with what has long been used in cockpit checklists [2]. In our own institution, we use linear cognitive aids whenever possible.…”
Section: Sedation For Transfemoral Aortic Valve Transplantation (Tavimentioning
confidence: 82%
“…We commend Miles et al for working to improve outcomes after transfemoral aortic valve implantation (TAVI) through increased use of conscious sedation rather than general anaesthesia (GA) [1]. Our practice has evolved in a similar fashion, with many patients undergoing this procedure without any sedation at all.…”
Section: Sedation For Transfemoral Aortic Valve Transplantation (Tavi)mentioning
confidence: 99%
See 1 more Smart Citation